THE RELATIONSHIP BETWEEN STUDENTS’ CYBERSECURITY COMPETENCE AND THE RISK OF PERSONAL DATA EXPLOITATION IN ONLINE LEARNING ENVIRONMENTS - Mesrawati Rifai; Regiena Sari; Dessy Pramudiani; Esther Hesline Palandi; Iwan Sonjaya (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the relationship between students’ cybersecurity competence and the risk of personal data exploitation in online learning environments. As digital platforms become more integral to education, the research aims to explore how students’ knowledge of cybersecurity influences their ability to protect personal information from online threats. Using a literature-based methodology, data was collected from academic journals, books, and studies related to cybersecurity and online learning. The findings show that students with higher cybersecurity competence are better at safeguarding their data, while those with lower knowledge are more vulnerable to exploitation. The study concludes that continuous cybersecurity education and institutional support are essential for enhancing students' data protection practices in online learning.